Forever Twelve: The Evers # 1 - McAnulty, Stacy (New York : Random House, 2023)
When twelve-year old Ivy attends West Archer Academy, she is determined to graduate in two years and eventually follow her hero Ruth Bader Ginsberg to the Supreme Court, but after her roommate introduces her to a group of students who are hundreds of years old, she is forced to reexamine her priorities.
new kids book 2025 winter.
Ages 8-12.
Grades 4-6.
Keywords: Schools -- Fiction; Fantasy; Boarding schools -- Fiction; Immortality -- Fiction; Novels; Fantasy fiction